Media ideals and other-sex peer norms among Belgian early adolescents: equating self-worth with attractiveness. Issue 4 (2nd October 2017) - Trekels, Jolien; Vangeel, Laurens; Eggermont, Steven
Abstract: The purpose of this study was to investigate how total amount of television and magazine exposure and heterosocial involvement (i.e., mixed-sex interactions) relate to the endorsement of dysfunctional appearance beliefs. We anticipated a double dose effect in that exposure to media would be related to more dysfunctional appearance beliefs among those who are frequently involved in mixed-sex interactions. A total of 1976 early adolescent boys and girls ( M age  = 11.77; SD = 1.04) participated in a cross-sectional study. Results indicated that the internalization of appearance ideals and appearance expectations of opposite-sex peers mediated the association between amount of television and magazine exposure and the endorsement of dysfunctional appearance beliefs. Heterosocial involvement did not, however, strengthen the influence of media exposure on early adolescents' body image.